(untitled) (Research, Society and Development, 2022)
Aim: To perform an integrative analysis of the most up to date scientific literature on attitudes towards dental prosthesis hygiene and oral hygiene in the elderly who use complete dentures in Brazil. Methodology: The bibliographic search was carried through the Scientific Electronic Library Online - SciELO and Google Scholar databases, using the following two combined controlled descriptors "oral hygiene", "complete prosthesis", "oral health", "geriatric dentistry" with the operator Boolean “AND”. Peer-reviewed research articles were included. The Cochrane Handbook guidelines were followed, when applicable. Results: The research resulted in finding 21 articles, of which 15 were excluded. The integrative review was structured with 6 articles for data extraction and critical and descriptive evaluation. Conclusion: The studies in this review suggested that elderly Brazilians have many oral health problems and a low level of knowledge about oral and prosthesis hygiene. An important gap in practical research was identified in the literature, with regard to oral care in elderly populations using complete dentures.